2001
DOI: 10.1007/s00464-001-9043-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcome after laparoscopic and open 360° fundoplication

Abstract: Laparoscopic 360 degrees fundoplication is as effective in treating reflux disease as open fundoplication. Six months postoperatively, no significant differences were seen in symptomatic or objective outcome. Long-term evaluation is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
1
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 6 publications
6
20
1
2
Order By: Relevance
“…However these complications included both major and minor and whether this difference is clinically significant remains to be seen. ONF still takes less time and is comparable to the constituent studies [13,14,19,[23][24][25][26][27][28][29][30][31][32][33][34][35] although this difference may disappear with progression along the learning curve as has been observed already in some European centres. Some studies have already shown a reduction of operating time for LNF [19].…”
Section: Resting Oesophageal Pressures After 5 Yearssupporting
confidence: 51%
See 2 more Smart Citations
“…However these complications included both major and minor and whether this difference is clinically significant remains to be seen. ONF still takes less time and is comparable to the constituent studies [13,14,19,[23][24][25][26][27][28][29][30][31][32][33][34][35] although this difference may disappear with progression along the learning curve as has been observed already in some European centres. Some studies have already shown a reduction of operating time for LNF [19].…”
Section: Resting Oesophageal Pressures After 5 Yearssupporting
confidence: 51%
“…There was no significant heterogeneity amongst trials [19,[30][31][32]35] and there was no significant heterogeneity (…”
Section: Overall Mortalitymentioning
confidence: 82%
See 1 more Smart Citation
“…Six months after surgery, the laparoscopic group reported significantly more sleep disturbances on the ad hoc questionnaire. In another publication from the same study, the authors used the Gastrointestinal Symptom Rating Scale (GSRS) [122] to analyze the differences in QoL between the two surgical approaches [143]. The GSRS scores did not differ between the two groups 1 and 6 months after surgery.…”
Section: Long-term Improvement Of Qol Is Not Different When Compared mentioning
confidence: 99%
“…During recent years, 14 publications from 9 randomized trials have dealt with the question of open or laparoscopic procedure for reflux disease [4,[12][13][14][15][16][17][18][19][39][40][41][42][43]. All of these trials have compared a full wrap by open or laparoscopic access and have shown similar or better outcomes from the laparoscopic approach as compared with open surgery.…”
Section: Discussionmentioning
confidence: 99%